AN ANNOTATED TRANSLATION OF FRANCES CHA’S IF I HAD YOUR FACE - FATMARIKKA PUTRI TOSANA (UPT P2M Politeknik Negeri Malang, 2022)
The writer translated 6,933 words from the novel. There are 81 problems that were grouped into 3 categories namely problems in understanding, transferring, and understanding and transferring. There are 27 problems in understanding, 37 problems in transferring, and 17 problems in understanding and transferring. There are 25 sentences containing problems analyzed. The writer used Baker’s translation strategies to solve those problems. The result revealed that not all of the translation strategies were used for analysis. From 8 strategies, there are 7 translation strategies used namely translation by a more general word (4 problems), translation by a more neutral/less expressive word (1 problem), translation by cultural substitution (1 problems), translation using a loan word or loan word plus explanation (3 problems), translation by paraphrase using related words (11 problems), translation by paraphrase using unrelated words (6 data), and translation by omission (1 data). The strategy of translation by illustration was not used in the analysis.